Probiotic Characterisation and Identification of Lactic Acid Bacteria in Panchagavya by 16S rRNA Sequencing - Muraleedharan, Varsha; Balasubramanian, Thamaraiselvi (Asian Journal of Biological and Life Sciences, 2025)
Aim: This study focuses on establishing and analyzing the synthesis of Gamma-Aminobutyric Acid using isolates from a synergistic combination, specifically concentrating on fermented panchagavya as a substrate for Lactic Acid Bacteria (LAB) to manufacture Gamma-Aminobutyric Acid. The study emphasizes the refinement and detailed evaluation of this method. Materials and Methods: Lactic acid bacteria, known for their ability to synthesize Gamma-Aminobutyric Acid and suitability for human consumption, were utilized. The synthesis of Gamma-Aminobutyric Acid was quantified using colorimetric data and thin-layer chromatography combined with ultraviolet-visible spectroscopy. Isolation of lactic acid bacteria was carried out using MRS (de Man, Rogosa, Sharpe) Medium as selective media, and their species were identified through 16S ribosomal RNA gene sequencing. Results: The panchagavya strains V2 and V7 demonstrated substantial Gamma-Aminobutyric Acid synthesis, evidenced by distinct zones corresponding to Gamma-Aminobutyric Acid under identical conditions. The 16S ribosomal RNA gene sequencing confirmed the isolates as Enterococcus faecium and Alcaligenes sp. Conclusion: Investigations into pH tolerance, NaCl tolerance, bile salt resistance, and sensitivity to phenolic compounds revealed that the V2 and V7 panchagavya cultures possess significant probiotic properties, qualifying them for commercial Gamma-Aminobutyric Acid production. This highlights a substantial industrial interest in scaling up Gamma-Aminobutyric Acid manufacturing.
Keywords: Alcaligenes sp.; Enterococcus faecium; Gamma-Aminobutyric Acid; Lactic acid bacteria